2005
DOI: 10.1097/01.mnm.0000167648.29853.93
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic related transitory left ventricular dysfunction in 201Tl gated SPECT

Abstract: Post-stress and at-rest LVEF are similar when all patients are considered but significant differences appear when patients are divided according to the results of the perfusion study. Normal and fixed defect patients have increased post-exercise LVEF. Patients with reversible defects have decreased LVEF, which is largely due to an increased ESV. Transitory left ventricular dysfunction is related to the presence of reversibility and may benefit from revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Instead of an increase, a decrease in stress LVEF may possibly be considered as impaired response to stress. This situation had been attributed to stunning according to some previously published studies [25][26][27][28][29][30][31][32][33][34][35][36]. In the present study we found a 4.4 ± 2.0% increase in mean SLVEF in group II (patients with normal perfusion), whereas 3.1 ± 3.0% and 6.0 ± 5.1% decreases were found in values of group I (cardiac syndrome X) and III (patients with ischaemia), respectively.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Instead of an increase, a decrease in stress LVEF may possibly be considered as impaired response to stress. This situation had been attributed to stunning according to some previously published studies [25][26][27][28][29][30][31][32][33][34][35][36]. In the present study we found a 4.4 ± 2.0% increase in mean SLVEF in group II (patients with normal perfusion), whereas 3.1 ± 3.0% and 6.0 ± 5.1% decreases were found in values of group I (cardiac syndrome X) and III (patients with ischaemia), respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…However, it is possible that, in patients with coronary artery disease after stress, LV dysfunction and transient cavity dilatation may develop and can last up to 45 min or even longer after stress [42]. In addition, some previous studies showed that PLVD to the G-SPECT images had been well correlated with myocardial perfusion abnormalities and degree of stenotic vessels in CAG in patients with coronary artery disease [25][26][27][28][29][30][31][32][33][34][35][36]. However, validity of this condition for patients with cardiac syndrome X has not been established.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation